Nanoparticle‐mediated surface modification of hydrophobic polymeric films/scaffolds and their application towards tissue engineering - Sengupta, P. (CSIR-National Chemical Laboratory, Pune, 2019)
Day by day, as the life expectancy is increasing, mankind is getting more exposed to dysfunctional organs, cosmetic deformities etc. Other than natural degenerative diseases, there are unexpected accidents, and also aesthetic reasons, which persuade people to take advantage of an externally procured (man-‐made) implant made up of polymeric scaffolds. Contact lenses, catheters, joint prosthetics, pacemakers, and stents are to name a few. Unfortunately, after installation, these implants may result in adverse reactions involving slow integration with the live tissue, infection, fibrosis, immune rejection etc. In the literature it has been well documented that imparting the necessary functionalities to the surface of such implants (surface modification) may allow us to circumvent these issues. Here, in this thesis we have harnessed the ‘surface modification techniques’ to convert the readily available, widely-‐used, implant-‐making polymers into a tissue-‐friendly one, and also understand it’s applications towards easy tissue integration, immune response, drug delivery, functional replacement etc.
Keywords: Tissue engineering polymer cell culture scaffold hydrophobic